Musical Composition Sandyaning Rang-Rang | Komposisi Musik Sandyaning Rang-Rang - I Putu Eka Julyana Putra (GHURNITA: Jurnal Seni Karawitan, 2022)
Tabuh kreasi Pepanggulan Sandyaning Rang-Rang this work is created from the amalgamation of the Sounth Balinese style and the North Balinese style. The uniqueness found in this work such as the techniques, spirit or disposition, as well as the characters contained in the two regions. Purpose of creation tabuh kreasi pepanggulan Sandyaning Rang-Rang this is to unify styles of South Balinese with North Balinese styles into the concept of the work tabuh kreasi pepanggulan by using the medium of expressing Balinese musical music. The method of creating this work uses the creation method of Alma M. Hawkins which consists of the assessment stage, the experimental stage, and the formation stage. From ths method, the stylist is creative by forming a work tabuh kreasi pepanggulan Sandyaning Rang-Rang. The result of the work process tabuh kreasi pepanggulan Sandyaning Rang-Rang this stylist is able to unite the South Balinese style and the North Balinese style into a single form tabuh kreasi pepanggulan Sandyaning Rang-Rang. Essentially tabuh kreasi pepanggulan Sandyaning Rang-Rang this is a medium to prove to the listeners that the South Balinese style and North Balinese style in the context of Balinese musical art can be united through concepts that have been designed and presented through dissemination.